PENGGUNAAN METODE MULTILAYER PERCEPTRON PADA PREDIKSI INDEKS SAHAM LQ45 - Pangaribuan, AB; A. Octa; B Hananto (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2019)
Forecasting stock prices is an analytical action that is needed as a first step to make decisions in determining the right moment to make buying and selling transactions on the stock exchange floor The amount of data used is 511 days in the period 31 May 2018 – 29 May 2020. This study aims to estimate three stock prices on a daily basis, namely PT. Telekomunikasi Indonesia (Persero) Tbk, PT.Astra International Tbk and PT. Kalbe Farma Tbk uses an artificial neural network model, namely Multilayer Perceptron (MLP)